Regional City: Conceptual and analytical framework - Luciane Borges; Mats Johansson; Krister Olsson (European Regional Science Association (ERSA), 2010)
For an increasing number of people the daily life operates simultaneously at two scales - a super-structural scale (the Regional City) and a sub-structural scale (the local place). 'Local places' refer here, foremost, to smaller settlements and towns throughout a region, rather than subcentres and explicit parts of a metropolitan centre. A Regional City provides a framework that contributes to shape local places physically and socially, and, at the same time, the physical and social character of various local places build-up and constitute the Regional City. Hence, a Regional City is recognized as a product of interdependencies between the regional level and local places. However, the concept Regional City is not clearly defined and its characteristics are rather vague, especially due to difficulties to establish these interdependences; therefore it requires further theoretical interpretation. The aim of this paper is to contribute to a further understanding of the Regional City and its characteristics. The analysis of the Regional City is based on some assumptions, e.g. (i) its development is uneven due to tensions between social and regional interests, and, thus, local places within the Regional City are asymmetrically reproduced and transformed; (ii) it is a social construction because it emerges from social practices, and, consequently it acknowledges a bottom up process in which the regional citizens play a key role; and (iii) it is individually perceived depending of how different activities are performed on both regional and local levels. These assumptions are discussed in the context of empirical observation from the Greater Stockholm Region (Mälardalen Region) in Sweden.
Keywords: 330